FTKPM shares expertise with Universitas Putra Indonesia YPTK students - Nadira Hana, Abdul Hamid (UMPSA, 2023)
PADANG, INDONESIA, 11 August 2023 - Staff and students from the Faculty of Manufacturing Engineering and Mechatronics Technology (FTKPM), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), recently organized a community service programme with students from Universitas Putra Indonesia, Yayasan Perguruan Tinggi Komputer (YPTK).